Pengaruh Performance Expectancy, Effort Expectancy,Facilitating Conditions, Social Influence, Attitude Towards Use, Pemakaian Aplikasi Zakat (GEMA EKONOMI, 2023)
The purpose of this study was to examine the factors that influence adolescents' intentions to use social networking media to understand online zakat campaigns that use creative animation. Data was obtained by distributing questionnaires online to users of the zakat application "Kitabisa.com" for the past year. The sample used in this study was 160 respondents. The sampling method used in this research is purposive sampling. The data analysis method used in this study is to analyze the influence between the variables owned by using the Multiple Linear Regression method with the help of SPSS 23 software. The results of this study conclude that Performance Expectancy has a positive effect on Youth's intention to use social media networks for understanding zakat online campaigns that use creative animations, Effort Expectancy have a positive effect on Youth's intention to use social media networks for understanding zakat online campaigns that use creative animations, Facilitating Conditions have a positive effect on Youth's intention to use social media networks for understanding zakat online campaigns that use creative animations, have an effect positive to, Social Influence has a positive effect on Youth's intention to use social media networks for understanding zakat online campaigns that use creative animations, Attitude To Use has a positive effect on Youth's intention to use social media networks for understanding zakat online campaigns that use creative animations.